Otimização da produção de biodiesel metílico a partir de óleos de fritura residuais (OFR) - Azeredo, Weine Amorim (2014)
Waste frying oils (WFO) consist an environmental liability, whose use in biodiesel production of adequate quality is compromised due to poor quality of the raw material. High levels of free fatty acids, degradation products of fatty acids, peroxides, hydroperoxides, metal and large amount of water in the feedstock compromise the quality of biodiesel produced. So the use of liquid-liquid extraction (LLE) as a pretreatment of the WFO using water as the solvent showed an efficient method in reducing the levels of polar compounds. After the OFR pre-treatment with water partition followed by the removal of the absorbed water via distillation under reduced pressure, experimental designs have been performed in steps acid esterification and transesterification alkaline thereby obtaining biodiesel samples with high contents methyl ester (96-98%). For the purification of biodiesel from WFO, the use of adsorbents such as silica and alumina proved efficient in the removal of water and reduction the acidity of the biodiesel, however reduced the oxidative stability. Distillation of biodiesel proved effective in reducing the water content, although reduced the oxidative stability of biodiesel.